Determinants of organic soil fertilization methods use over time and in the face of climate vulnerability - Sharna, Shaima Chowdhury; Maraseni, Tek; Radanielson, Ando Mariot (Elsevier, 2024)
Implementation of environment-friendly soil organic matter (SOM) enhancing technologies (SOMET) is crucial for addressing soil degradation. This study aims to examine the usage status of SOMET (i.e., organic fertilizer, manure, and compost) from the dimension of long-term non-usage, dis-usage, late-usage and long-term usage and identify the drivers of these four behaviors of usage. We utilized national representative datasets of 1659 Bangladeshi rice-farmers for the periods of 2013, 2016 and 2020 with climate hazards data. Households were categorized into long-term non-user (48%) who does not practice SOMET in any of three survey years, dis-user (29%) as the households who abandon SOMET after practicing a period of time, late-user (20%) for the households who apply SOMET a few years later than their peer, long-term user (3%) as the households who practice SOMET for three survey years. Ordered logit model was used to quantify drivers of likelihood of being the four above defined categories. SOMET use has been found to be highly constrained by climate hazards. Flood depth, salinity, heavy rainfall, storm and cyclone vulnerability decrease likelihood of long-term use and late-use while increase the probability of long-term non-use and dis-use (p≤0.01). Alternatively, the likelihood of long-term non-use and dis-use are 12% and 4% lower in drought-prone areas. Increasing drought experiences increase the probability of long-term use and late-use (p≤0.01). Higher SOM level decreases long-term non-use but induces dis-use. Other major drivers of SOMET long-term use are older household head, more educated women in households, larger farm-size, and higher livestock values. Considering these factors in developing and implementing policies could be instrumental in promoting SOMET application at farm-level. Long-term use is context-specific with various climate and socio-economic factors, thus, designing policies and strategies should emphasize contextual variations to promote usage continuities